"Dogs Don't Vote": Diatribe and Animality in Peroratas, by Fernando Vallejo. Issue 3 (2nd July 2020) - Maier, Gonzalo
Abstract : This article focuses on the animal rights diatribes included by Fernando Vallejo in Peroratas (2013), a volume that contains speeches and editorial texts published in both Spain and Latin America. On the one hand, the article analyses to what end he directs his diatribes. On the other, it proposes a reading in which Vallejo's animal rights tirades are distanced from the dialogic will that characterises the diatribe and instead conform to a style of attack and deprecation. In fact, his drawn-out speeches demand not legislation that attends to a dignified life, but a transposition that takes rights from humans and grants them to wild and domestic animals. While they may well be read from a perspective that exclusively privileges animal rights, I propose to read Vallejo's diatribes with an eye towards a cynical vocation – with important ironic elements – derived from their regionalist filiation. More broadly, I begin with an eye to the way in which they oppose 'positive thinking' and indirectly question the ethic of happiness that rules in certain cultural discourses.